An Economical Assessment Model for Elementary Physical Education. Issue 6 (24th July 2022) - Allen, Ray; Ferkel, Rick; Fisher, Kevin; Wawersik, Andrew
Abstract: The purpose of this paper is to present an assessment system that enables physical education programs to collect data capable of meeting their assessment. Assessment at the elementary level is a daunting task. Practitioners are charged to teach multiple objectives across all learning domains to hundreds of students in multiple grades in a limited amount of time. Conscientious teachers attempt to collect valid, reliable data that documents growth, defends their program to decision-makers, and guides program improvement and professional development efforts.